Neotype designation and redescription of Inostemma indicum (Platygastroidea: Platygastridae) parasitizing ivy gourd gall midge - Kamalanathan, Veenakumari; Shylesha, A. N.; Mohanraj, Prashanth (Zootaxa, 2018)
Inostemma indicum Mani, a parasitoid of Neolasioptera cephalandrae Mani (Diptera: Cecidomyiidae), collected from stem galls of ivy gourd (Coccinia grandis (L.) Voigt (Cucurbitaceae)) was described by Mani in 1941. The original description is scanty and ambiguous, with little diagnostic value. The holotype, a dissected female mounted on a slide, is lost. It is redescribed with illustrations and a neotype is designated. The previously unknown male is also described.